Analisis Kualitas Software Electronic Traffic Law Enforcement di Ditlantas Polda Jawa Timur Menggunakan Teori McCall - Agustino, Jonathan Fajar; Khuntari, Diana (Jurnal Ilmiah Multimedia dan Komunikasi, 2023)
As technology develops, humans are required to be smarter in their activities, doing works, and dealing with various existing problems. Technology is also increasingly being used as a tool to support success in various fields, including government. The government applies technology in regional governance to create a smart city. The government has developed several things that used to be conventional to become electronic-based, one of which is the ticketing system. Limitations on convention tickets as well as the large number of motorized vehicle users and traffic violations in Surabaya finally made the Surabaya Police work together with the Surabaya Transportation Agency (Dishub) to trigger the Electronic Traffic Law Enforcement system or Electronic Ticketing, commonly known as E-TLE. One of the success factors of the system is the quality of the system itself. This study aims to analyze the E-TLE software implemented in Surabaya to determine the quality of the software. The approach used to carry out the analysis is the theory of software quality according to McCall. The research method used in this research is qualitative research by collecting data using interviews, observation, and classification. The source of this research is the operator as well as designing the E-TLE software. The results show that the quality of the E-TLE software has good scores in the aspects of correctness, reliability, efficiency (data search and memory usage), integrity, usability, maintainability, flexibility, portability, reusability, and interoperability. However, there are slight deficiencies in the usability aspect (there is no integration between agencies) and lack of testability. To improve the quality of E-TLE, it is necessary to optimize page loading, add features for integration between agencies, and test to determine software grade.